#mycityoftomorrow. A think tank on cities and territories of tomorrow - Francesco Alberti; Stefania Cupillari; Eleonora Giannini; Sara Naldoni; Lorenzo Nofroni (Agathón)
The pandemic of Covid-19 represents a chance to rethink the equilibrium of our territories and cities. The sudden revision of rules of social coexistence, the temporary suspension of activities, the modification of everyday gestures, physical public spaces replaced by digital spaces, are only some of the phenomena which happened simultaneously in 2020 due to the pandemic. From the will to reflect in a collective way on the implications of the health emergency on our ways of living, and from the project will to use the crisis as an experimentation field of new practices of sharing and elaboration of future urban scenarios, the campaign #MyCityofTomorrow of the spin-off Urban LIFE (University of Florence) was designed as an online platform of open dialogue on the topics which inform urban design and planning, in its broader sense, a discussion table to orient the restarts towards a more sustainable future.